Factor analysis of young academician consumption behaviors toward organic food and it’s obstacles - Anas Hidayat; Tony Wijaya (Management Development Centre (MDC) Department of Management, Faculty of Business and Economics Universitas Islam Indonesia, 2023)
Purpose – This research aimed to explore environmentally friendly behaviors toward organic food consumption among the young academicians dominant in the higher education environment. This study also aims to explore the obstacles in consuming organic food qualitatively. Design/methodology/approach – This research uses mix methods by combining two analytical methods. The population was academicians consuming organic food in Indonesia. This research employed the purposive sampling technique. The criteria used in this study determine the sample as young academicians who are still active in higher education, care about a health issue, and regularly buy products for daily consumption, or are called regular consumers. Primary data were collected through surveys using closed and open questionnaires. The study uses mix methods consisting of descriptive qualitative and factor analysis were used in the data analysis. Findings – The results show that the factors influencing academicians' organic food consumption are responsibility for the environment, subjective norms, information or knowledge, the impact of consumption, behavioral control, and the values oriented towards nature. However, still aspects may become obstacles in consuming organic food, namely organic product price, availability, information or knowledge, and trust. Originality/value – This research offers a study of consumption from young academics, which is not widely studied, even though young academics have an important role in environmentally-friendly behavior. This research also investigated several reasons that became obstacles to the young academician behavior of consuming organic food. Research limitation – This research has several limitations, such as the variation of the sample. Cultural differences bring consequences for differences in environmentally friendly behavior because of the values that are different. Future research can compare the consumption behavior of young academicians based on the country and cultural differences. Practical implication – Based on the findings, some practical recommendations for increasing environmentally friendly consumption are made through promoting organic consumption behavior's benefits and environmental impacts. Environmentally friendly teaching material needs to be considered part of the learning process to improve academic knowledge. Young academician can become promotional agents to shape environmentally friendly consumption behavior, especially organic products. Another contribution as an agent of change in behavior in the world of education is also acting as a segmentation pattern for academic groups.